(untitled) (Altre Modernità, 2015)
Simone Cimotto, The Italian American Table. Food, Family, and Community in New York City (Urbana, Chicago, and Springfield, University of Illinois Press, 2013, pp. 265, ISBN 978-0-252-07934-4)